Peningkatan Niat Pembelian melalui Website - Wirawan Wirawan (The Winners, 2013)
In globalization era, technology is rapidly growing. Nowadays many companies use technology in their business with the purpose to support internal and external activities, such as online sales. Currently, the level of competition in the field of online sales is getting bigger because there are many companies get into the market. The purpose of this study is to help new website of PT Pos Indonesia (Galeripos) face competition and increase the intention of visitor to visit Galeripos and the number of transaction there as well. This study was conducted to know how website quality and perceived risk influence online trust of web visitors and the impact on online purchase intention. The method used in this research is path analysis. Data had collected by distributing questionnaires through social media. As conclusion, website quality, perceived risk, and online trust, individually and simultaneously, have significant influence on online purchase intention.